2021
DOI: 10.1038/s41467-021-27349-7
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor regulates PD-L1 and MHC-I in pancreatic cancer cells to promote immune evasion and immunotherapy resistance

Abstract: Despite unprecedented responses of some cancers to immune checkpoint blockade (ICB) therapies, the application of checkpoint inhibitors in pancreatic cancer has been unsuccessful. Glucocorticoids and glucocorticoid receptor (GR) signaling are long thought to suppress immunity by acting on immune cells. Here we demonstrate a previously undescribed tumor cell-intrinsic role for GR in activating PD-L1 expression and repressing the major histocompatibility complex class I (MHC-I) expression in pancreatic ductal ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…GCs can enhance the expression of PD‐L1 in DCs through the GC‐induced leucine zipper 46 and prevent antigen‐specific T lymphocyte response 47 . Furthermore, the GC receptor can regulate PD‐L1 and MHC‐I in pancreatic cancer cells to promote immune evasion and immunotherapy resistance 48 . Interestingly, according to another study on alcohol‐induced GC feedback circuit, FKBP51 was involved in glucocorticoid regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCs can enhance the expression of PD‐L1 in DCs through the GC‐induced leucine zipper 46 and prevent antigen‐specific T lymphocyte response 47 . Furthermore, the GC receptor can regulate PD‐L1 and MHC‐I in pancreatic cancer cells to promote immune evasion and immunotherapy resistance 48 . Interestingly, according to another study on alcohol‐induced GC feedback circuit, FKBP51 was involved in glucocorticoid regulation.…”
Section: Discussionmentioning
confidence: 99%
“…47 Furthermore, the GC receptor can regulate PD-L1 and MHC-I in pancreatic cancer cells to promote immune evasion and immunotherapy resistance. 48 Interestingly, according to another study on alcoholinduced GC feedback circuit, FKBP51 was involved in glucocorticoid regulation. They found that FKBP51 inhibition by SAFit2 can block GC signalling pathways and reduce alcohol consumption.…”
Section: Fkbp51 Is Necessary In Fk506mediated Pd-l1 Regulationmentioning
confidence: 99%
“…In melanoma, regorafenib inhibits JAK1/2-STAT1 and MAPK signaling by targeting the RET-Src axis, consequently attenuating IFN-γ-induced PD-L1 expression [ 146 ]. A previous study has reported that the glucocorticoid receptor inhibitor mifepristone and dual ICB act synergistically in PC to inhibit PD-L1 expression while promoting cytotoxic T cell infiltration and activity, enhancing antitumor immunity [ 147 ]. Metformin activates AMPK, which phosphorylates S195 of PD-L1, resulting in abnormal PD-L1 glycosylation [ 109 ].…”
Section: Targeting Pd-l1 and The Pd-l1 Regulatory Pathway For Cancer ...mentioning
confidence: 99%
“…In a solid tumor model of stress-induced resistance to anti–PD-1 mAbs, β2-AR blockade up-regulated the ratio of effector CD8 + T cells to CD4 + T reg cells, decreased CD8 + TILs expressing PD-1, and thus reduced treatment resistance in the stressed mice ( 77 ). GR signaling has been shown to cause increased PD-L1 and decreased major histocompatibility complex I expression in pancreatic ductal adenocarcinoma models, thus promoting tumor immune escape and impairing the effects of anti–PD-1 treatment ( 78 ). GR blockade can induce an immunologically active TME to reverse the resistance to anti–PD-1 mAbs in mice caused by GC administration or social distress ( 22 , 78 ).…”
Section: Psychological Distress and Cancermentioning
confidence: 99%
“…GR signaling has been shown to cause increased PD-L1 and decreased major histocompatibility complex I expression in pancreatic ductal adenocarcinoma models, thus promoting tumor immune escape and impairing the effects of anti–PD-1 treatment ( 78 ). GR blockade can induce an immunologically active TME to reverse the resistance to anti–PD-1 mAbs in mice caused by GC administration or social distress ( 22 , 78 ). Distress attenuated the antitumor effects of CpG-C, a novel Toll-like receptor-9 immunostimulatory agent, in metastatic tumor models by impairing CpG-C–induced NK-cell activity, which could be reversed by simultaneous inhibition of COX-2, as well as GR and β-AR signaling ( 33 ).…”
Section: Psychological Distress and Cancermentioning
confidence: 99%